2023
DOI: 10.1007/s10875-023-01614-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined Immunodeficiency Caused by a Novel Nonsense Mutation in LCK

Baerbel Keller,
Shlomit Kfir-Erenfeld,
Paul Matusewicz
et al.

Abstract: Mutations affecting T-cell receptor (TCR) signaling typically cause combined immunodeficiency (CID) due to varying degrees of disturbed T-cell homeostasis and differentiation. Here, we describe two cousins with CID due to a novel nonsense mutation in LCK and investigate the effect of this novel nonsense mutation on TCR signaling, T-cell function, and differentiation. Patients underwent clinical, genetic, and immunological investigations. The effect was addressed in primary cells and LCK-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Recent studies in humans identified patients with partial or complete LCK deficiency. Interestingly, CD4 expression was decreased in T cells from LCK deficient patients, suggesting that recruited LCK plays a crucial role in stabilizing CD4 on the surface of T cells ( Keller et al, 2023 ; Lanz et al, 2023 ; Lui et al, 2024 ). CD4-mediated interactions with CD3 increase the duration of cognate TCR–HLA class II interplay and therefore ensure scalable signaling which determines the duration and magnitude of responses of CD4 + T cells ( Glassman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in humans identified patients with partial or complete LCK deficiency. Interestingly, CD4 expression was decreased in T cells from LCK deficient patients, suggesting that recruited LCK plays a crucial role in stabilizing CD4 on the surface of T cells ( Keller et al, 2023 ; Lanz et al, 2023 ; Lui et al, 2024 ). CD4-mediated interactions with CD3 increase the duration of cognate TCR–HLA class II interplay and therefore ensure scalable signaling which determines the duration and magnitude of responses of CD4 + T cells ( Glassman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%